2019
DOI: 10.3390/s19091975
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Acoustic Sensing of Strain at Earth Tide Frequencies

Abstract: The solid Earth strains in response to the gravitational pull from the Moon, Sun, and other planetary bodies. Measuring the flexure of geologic material in response to these Earth tides provides information about the geomechanical properties of rock and sediment. Such measurements are particularly useful for understanding dilation of faults and fractures in competent rock. A new approach to measuring earth tides using fiber optic distributed acoustic sensing (DAS) is presented here. DAS was originally designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…The present DAS measurement indicates enough sensitivity in the low frequency range down to , and supports the possibility of detection of such long-period phase changes in a fiber-optic cable. It has been reported that a long-period strain oscillation induced by the earth tide can be detected by DAS, albeit being performed in a laboratory experiment 47 .…”
Section: Resultsmentioning
confidence: 99%
“…The present DAS measurement indicates enough sensitivity in the low frequency range down to , and supports the possibility of detection of such long-period phase changes in a fiber-optic cable. It has been reported that a long-period strain oscillation induced by the earth tide can be detected by DAS, albeit being performed in a laboratory experiment 47 .…”
Section: Resultsmentioning
confidence: 99%
“…The broadband nature of DAS has largely been overshadowed by the use of DAS in active‐source experiments at high frequencies ( f>10 Hz; T<0.1 s). The long‐period frequency response of the DAS method has been demonstrated in recordings of teleseismic earthquakes (Ajo‐Franklin et al, ; Jousset et al, ) and laboratory and field pump tests (Becker et al, ; Becker & Coleman, ). To date, the longest period earthquake signal observed with DAS used a dark fiber DAS array in the Mojave Desert to capture propagating surface waves down to T=200 s (Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the longest period earthquake signal observed with DAS used a dark fiber DAS array in the Mojave Desert to capture propagating surface waves down to T=200 s (Yu et al, ). Recently, Becker and Coleman () showed that DAS can record tidal periods ( T=4.3×104 s) in a laboratory setting, albeit with a strain amplitude 7.1em×.1em103 times greater than the solid Earth tide.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the instrument response of DAS is broader than that of traditional receivers. However, it requires careful treatment and calibration as the fiber properties, casing, and installation method can influence it [31,[48][49][50]. A virtual DAS receiver is a single-axis measurement sensor, which is sensiti strain (or strain-rate) along the direction of the fiber.…”
Section: Introductionmentioning
confidence: 99%